miR-1225-3p regulates fibrosis in mesangial cells via SMURF2-mediated ubiquitination of ChREBP in diabetic kidney disease - Juntai Zhang; Yan Cai; Yan Qin; Jie Liu; Jie Ding; Mengying Xu; Li Yang; Yuanxin Zheng; Xi Zhang (Renal Failure)
Background Diabetic kidney disease (DKD), characterized by mesangial fibrosis and renal dysfunction, is a major microvascular complication of diabetes. Studies have shown that miRNAs are closely related to the progression of DKD. Therefore, in this study, we aimed to explore whether miR-1225-3p can regulate Smad ubiquitin regulatory factor 2 (SMURF2)-mediated carbohydrate response element binding protein (ChREBP) ubiquitination through Rho GTPase-activating protein 5 (ARHGAP5) to affect fibrosis in DKD.Methods DKD mice were established by intraperitoneally injecting streptozocin (STZ), and a DKD cell model was generated by culturing in media supplemented with 25 mmol/L glucose (high glucose, HG). StarBase was used to predict the target binding sites between miR-1225-3p and ARHGAP5, and a dual-luciferase reporter gene assay was used to verify this relationship. Western blotting, RT–qPCR, flow cytometry, immunoprecipitation, ELISAs, HE staining, and Masson staining were used to detect relevant indicators.Results ARHGAP5 and SMURF2 expression was decreased, but ChREBP was highly expressed in the renal tissue of DKD mice and HG-induced mouse mesangial cells (MMCs). miR-1225-3p could target and regulate the transcription of ARHGAP5, and an association between ARHGAP5 and SMURF2 was revealed. miR-1225-3p facilitated fibrosis and oxidative stress in MCCs by inhibiting ARHGAP5. In addition, SMURF2 promoted the ubiquitination of HA-ChREBP, and miR-1225-3p facilitated fibrosis and oxidative stress by mediating the ARHGAP5/SMURF2-mediated ubiquitination of ChREBP in MCCs. Furthermore, the miR-1225-3p inhibitor inhibited fibrosis and inflammation in the renal tissues of DKD mice.Conclusion miR-1225-3p facilitates fibrosis and oxidative stress by mediating ARHGAP5/SMURF2-mediated ubiquitination of ChREBP.